Effect of the aqueous extract of Sida cordifolia on liver regeneration after partial hepatectomy - Silva,Renata Lemos (2006)
PURPOSE: The use of medicinal plants for the treatment of human diseases has increased worldwide. Many of them are used by oral administration and, after absorption, may affect many organs. Therefore, this study aimed at assessing the effects of the aqueous extract of Sida cordifolia leaves, popularly known in Brazil as "malva-branca", on liver regeneration. METHODS: Twenty rats were divided into four groups: control, Sida100, Sida200 and Sida400 groups. All animals were submitted to oral administration of distilled water, 100, 200 and 400 mg/kg of the aqueous extract of Sida cordifolia, respectively. Immediately after this, they underwent 67% partial hepatectomy. Twenty four hours later, their livers were removed. Hepatic regeneration was assessed by immunohistochemical staining for proliferating cell nuclear antigen (PCNA) using the PC-10 monoclonal antibody. RESULTS: Sida100 and Sida200 groups disclosed higher liver regeneration indices than control group (p<0.001 and p<0.05, respectively). CONCLUSION: The aqueous extract of Sida cordifolia stimulates liver regeneration after 67% partial hepatectomy in rats.